2007
DOI: 10.2989/ajrfs.2007.24.3.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Induced chemical defences in Colophospermum mopane trees

Abstract: A field experiment was conducted in which Mopane (Colophospermum mopane) trees were subjected to three different canopy treatments:felling of trees at a mean height of 0.7m above ground level, felling at a height of 2m, or pruning of selected branches. These treatments were intended to simulate wood harvesting by local communities, pollarding by elephants, and browsing by herbivores, respectively. The foliar concentrations of total phenol, condensed tannin and protein-precipitating tannin were tracked for thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
1
26
1
Order By: Relevance
“…On the x-axis, the eight sample periods from the beginning of February (end of the wet summer period) until the end of May (mid dry winter period) are displayed: 1 means the first 2 weeks of the month and 2 the last 2 weeks although digestion of especially hindgut fermenters is assumed to be negatively affected under high concentrations of condensed tannins (Duncan and Poppi 2008). It has been suggested that elephant can tolerate condensed tannins (Lagendijk et al 2005;Wessels et al 2007). Styles and Skinner (2000) and Rooke et al (2004) suggested that browsers can produce salivary tannin-binding proteins as an adaptation to tannin-rich forage.…”
Section: Month % Monocots In Faecesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the x-axis, the eight sample periods from the beginning of February (end of the wet summer period) until the end of May (mid dry winter period) are displayed: 1 means the first 2 weeks of the month and 2 the last 2 weeks although digestion of especially hindgut fermenters is assumed to be negatively affected under high concentrations of condensed tannins (Duncan and Poppi 2008). It has been suggested that elephant can tolerate condensed tannins (Lagendijk et al 2005;Wessels et al 2007). Styles and Skinner (2000) and Rooke et al (2004) suggested that browsers can produce salivary tannin-binding proteins as an adaptation to tannin-rich forage.…”
Section: Month % Monocots In Faecesmentioning
confidence: 99%
“…However, mopane contains high levels of condensed tannins and other secondary compounds compared to other plant species. This condensed tannin concentration fluctuates between seasons (Ferwerda et al 2005;Codron et al 2006;Wessels et al 2007). Mopane maintains its foliage well into the dry season, providing an important food source for browsers and intermediate feeders both in the wet season (summer) and dry season (winter).…”
Section: Introductionmentioning
confidence: 99%
“…However, very few studies have quantified the relationship between browsing by elephants (or simulation thereof) and either growth rate or nutritional value of individual trees, and the results are inconsistent. Increasing the severity of simulated elephant browsing of Colophospermum mopane trees once in the growth season led to increased investment in CBSMs, which remained elevated for 2 years (Wessels et al 2007). In contrast, severe browsing (including branch breakage) by elephants had no effect on either N or CBSMs in C. mopane and led to increased shoot growth compared with no browsing (Hrabar et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While defoliation may induce defences in woody plants (Ward and Young 2002;Wessels et al 2007), severe browsing has been reported to have the opposite effect, by causing either increased N concentrations or reduced tannin concentrations in individual plants (du Toit et al 1990;Danell et al 2003;Persson et al 2005). Therefore, heavily browsed plants may switch to a vegetative state characterised by N-rich/Cpoor tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Increases in CBSM concentrations, sometimes associated with decreases in [N] and [P], have been detected in the same season of browsing/clipping or in the growing season after browsing/ clipping (e.g. Bryant et al 1991;Wessels et al 2007), but the reverse pattern, sometimes associated with increased [N] and shoot growth, has also been detected (e.g . Scogings 1998;Rooke and Bergström 2007).…”
Section: Introductionmentioning
confidence: 99%